Modelo para os canais de potássio para respostas rápidas de células de Sertoli de ratos imaturos - Taques, Barbara Ogliari Martins (2023)
Sertoli cells are essential for the male reproduction system as they provide morphological support and nutrients for germ cells to guarantee ongoing spermatogenesis. The aim of this work was to predict the electrical properties at the plasma membrane that trigger Sertoli cell rapid responses by involving ionic channels. The rapid responses of Sertoli cells in culture were monitored using patch clamp electrical measurement and compared to data obtained using pharmacological tools from intact seminiferous tubules. A mathematical model was used to define the roles of potassium channels and the ATP-dependent Na+/K+ pump in these responses. Mathematical data verification was also performed to determine the resting and hormonal stimulated membrane potentials of Sertoli cells in the intact seminiferous tubules and of Sertoli cells in culture (patch clamp measurements). The prediction of these data based on mathematical modeling demonstrated, for the first time, the involvement of potassium channels and the activation of Na+/K+ pump in the hyperpolarization of Sertoli cells and their consequent rapid responses. Moreover, the mathematical analysis showing the involvement of ionic balance in the rapid responses of these cells to hormones, such as follicle-stimulating hormone, is consistent with previous reports obtained using pharmacological techniques in Sertoli cells.